Structural features of two major nucleolar organizer regions (NORs), Nor‐B1 and Nor‐B2, and chromosome‐specific rRNA gene expression in wheat. (27th October 2018) - Handa, Hirokazu; Kanamori, Hiroyuki; Tanaka, Tsuyoshi; Murata, Kazuki; Kobayashi, Fuminori; Robinson, Stephen J.; Koh, Chu S.; Pozniak, Curtis J.; Sharpe, Andrew G.; Paux, Etienne; Wu, Jianzhong; et al.
Summary : The reference genome sequence of wheat 'Chinese Spring' (CS) is now available (IWGSC RefSeq v1.0), but the core sequences defining the nucleolar organizer regions (NORs) have not been characterized. We estimated that the total copy number of the rDNA units in the wheat genome is 11 160, of which 30.5%, 60.9% and 8.6% are located on Nor‐B1 (1B), Nor‐B2 (6B) and other NORs, respectively. The total length of the NORs is estimated to be 100 Mb, corresponding to approximately 10% of the unassembled portion of the genome not represented in RefSeq v1.0. Four subtypes (S1–S4) of the rDNA units were identified based on differences within the 3′ external transcribed spacer regions in Nor‐B1 and Nor‐B2, and quantitative PCR indicated locus‐specific variation in rDNA subtype contents. Expression analyses of rDNA subtypes revealed that S1 was predominantly expressed and S2 weakly expressed, in contrast to the relative abundance of rDNA subtypes in the wheat genome. These results suggest a regulation mechanism of differential rDNA expression based on sequence differences. S3 expression increased in the ditelosomic lines Dt1BL and Dt6BL, suggesting that S3 is subjected to chromosome‐mediated silencing. Structural differences were detected in the regions surrounding the NOR among homoeologous chromosomes of groups 1 and 6. The adjacent regions distal to the major NORs were expanded compared with their homoeologous counterparts, and the gene density of these expanded regions was relatively low. We provide evidence that these regions are likely to be important for autoregulation of the associated major NORs as well as silencing of minor NORs. Significance Statement: Based on the wheat reference genome sequence (IWGSC RefSeq v1.0), we characterized the structure of two major nucleolus organizer regions, loci encoding rRNAs, and their surrounding regions in the wheat genome and identified the composition of rDNA units that display chromosome‐specific expression patterns. These results lead to an understanding of the nucleolar dominance associated with allopolyploidization during the evolution of wheat.